Motyw wspomnień w późnej liryce Piotra Wiaziemskiego - Toczyńska-Pęksa, Anna (Acta Neophilologica, 2020)
This article discusses the motif of memory which can be noticed in Vyazemsky’s late poetry: poems written in the 1850s, 1860s and 1870s. Peter Vyazemsky was a poet, literary critic, and letter writer appreciated for his talent not only in Russia but also in Poland. In his late poetry Vyazemsky recalls his close friends, his beloved mother as well as places he visited during journeys abroad. The poet presents his thoughts about his own life, ancestors, and human life in general. The poems are strongly influenced by the ideas of Romanticism.